Experimental study of heat transfer enhancement by inserting metal chain in heat exchanger tube - Ghitheeth, Ali H.; Fawzi, Mas; Wahhab Aljibory, Mohammed (2020)
Heat transfer augmentation in heat exchangers is important in many large industrial applications and many studies have been conducted on this subject. In this paper, an experimental study was used to verify the increased heat transfer of a circular heat exchanger tube with the insertion of metal chains, under turbulent flow conditions. A rig was designed and fabricated to investigate the effects of using the metal chain as turbulators inside the heat exchanger pipe, on heat transfer performance and on fluid flow behavior. The metal chains used were of different lengths of chain ring and different diameters of ring wire. Five ring length/tube diameter ratios (P/D) were used, (1, 2, 3, 4 and 5). Two wire diameter /tube diameter ratios (t/D) were used in this work (0.1 and 0.15). Heavy fuel oil (HFO) was used inside the tube, flowing at 30 °C with uniform tube wall temperature. The Reynolds numbers tested were between 5,000 and 15,000. The results showed the thermal enhancement factor (η) decreased with increasing Reynolds number for all cases, depending on lengths of chain ring (P) and thickness the weir chain (t) values. A maximum thermal enhancement factor (η) was found with a metal chain at P/D=3 and t/D= 0.15. The results also show that P/D=1 and t= 4mm, give the highest Nusselt number.